Reducing Pain in Postoperative Femoral Fracture Patients with Spiritual-Based Relaxation Breathing - Mahyuvi, Tata; Marta, Dony Kristiya (Journal of Applied Nursing and Health, 2023)
Background: Fractures occur due to trauma or physical activity with excessive pressure on the bone, including collisions, beatings, falls, irregular or tilted positions, dislocations, withdrawals, and abnormal bone weakness (pathological fractures). This study aims to analyze the effect of Breathing Relaxation spiritual-based on reducing pain scale in patients with postoperative femoral fractures. Methods:  A quasi-experiment with a one-group pretest-posttest design technique constitutes the study design. Population All postoperative femur fracture patients at Mitra Medika Hospital Bondowosoof 30 people. The sample size is 24 respondents. The sampling technique is Consecutive Sampling. Intervention is given effect Breathing Relaxation spiritual based. The analysis used the Wilcoxon Signed Ranks Test with a significant value of ‎α <0.05. Results:  The pre and post-pain scale test using the Wilcoxon Signed Ranks Test obtained a p-value of 0.000, which means the effect of Breathing Relaxation Spiritual-Based Changes in Pain Scale in Postoperative Femur Fracture Patients. Conclusion: Breathing Relaxations are spiritually based and effective in reducing Pain Scale in Postoperative Femur Fracture Patients. This method is very good when applied in hospitals to develop nursing knowledge.